Analisis Implementasi Standar Pelayanan Publik Pada Lembaga Pelatihan Kerja Wajo Intelektual Mandiri - Mastura Karateng; Muktamir Usman; Burhanuddin Burhanuddin (Journal of Research and Development on Public Policy, 2024)
People often complain about the quality of public services due to several factors, both factors originating from an institution's system and the human resources who work in it. We often encounter services that take a long time or require conditions that make people feel burdened. Therefore, it is necessary to implement Public Service Standards in every institution or organization. The existence of public service standards provides open access to information to the public, so that in a service both requirements, procedures, costs and time periods can be measured and known to the public without experiencing confusion or demands. community supervision in its implementation.